Transmigration of mandibular canine: A case report and review of literature - Shivayogi Charantimath (Wolters Kluwer Medknow Publications, 2009)
Transmigration of mandibular permanent canine is a rare event, the etiology of which is not clear. Pre-eruptive migration of a tooth across the midline is termed "transmigration. Here we present a case report. The literature on this rare condition is reviewed, its etiological possibilities are discussed.